Theological consequences of Darwinism — “Darwin’s God” by Cornelius G. Hunter - Gołaszewski, Filip (Hybris, 2023)
The aim of this article is to present Darwinian theodicy according to Cornelius G. Hunter. Hunter’s book was translated to polish by Józef Zon and it was published by Fundacja En Arche in 2021. Article presents the critical reading of Hunter’s book. It claims that Hunter’s main thesis is superficial and the arguments to support it are insufficient. Firstly, the historical background for the problem of theodicy is being introduced. Moving from St. Augustine and Leibniz some of the 20th century and contemporary attempts to the problem of evil are being discussed. This delineates the context for Hunter’s attempt to present Darwinism as an example of the philosophical theodicy. Secondly, main ideas of Hunter’s Darwin’s God are presented. Special focus is being put to the problem of metaphysical and theological implications but also hidden assumptions behind theory of evolution. In the end the article highlights some of the weakness regarding Hunter’s narrative about the cultural sources of Darwinian deism are presented. Mainly, the historical simplifications regarding nineteenth century atheism and one logical gap in Hunter’s argumentation. Hunter argues that Darwinism is based on some metaphysical assumptions and for that reason it cannot be considered as an example of science. At the same time Hunter fails to give an example of scientific theory that is entirely free from metaphysical assumptions. Therefore it seems that his critique of Darwinism fails to deliver a convincing argument.